Ensuring continuity in science education (on example of physics curriculum) - Nurmukhamedova, Zhanara; Nurbayeva, Dilara; Yerzhenbek, Bulbul (Institute of Advanced Engineering and Science, 2024)
The relevance of the research stems from the need to study the issues of continuity of the school and university curricula content in science disciplines on the example of the “physics” course. This study aims at identifying the principles of continuity of the content of school curricula and higher education programs in natural sciences in the example of the “physics” course, as well as disclosing methods to ensure the continuity of secondary and higher education in the Republic of Kazakhstan. The primary method in this study is system analysis, which is applied to examine the continuity of the school and university science curricula content, using the “physics” course as an example. Moreover, a theoretical analysis of recent scientific publications was carried out in the research process. The study deals with the problem of maintaining continuity in the general secondary education curricula in the field of natural sciences based on a renewed education program. The study presents the results of the analysis in the form of methodological suggestions and reveals possible barriers to the implementation of lifelong learning.